2015
DOI: 10.1038/bmt.2015.204
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of deferasirox in non-thalassemic patients with elevated ferritin levels after allogeneic hematopoietic stem cell transplantation

Abstract: Elevated serum ferritin contributes to treatment-related morbidity and mortality after allogeneic hematopoietic stem cell transplantation (HSCT). The multicenter DE02 trial assessed the safety, efficacy and impact of deferasirox on iron homeostasis after allogeneic HSCT. Deferasirox was administered at a starting dose of 10 mg/kg per day to 76 recipients of allogeneic HSCT, with subsequent dose adjustments based on efficacy and safety. Deferasirox was initiated at a median of 168 days after HSCT, with 84% of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 52 publications
3
30
0
Order By: Relevance
“…1,4,5,27 In this report, the increases in serum creatinine were all below 2 times ULN. Patients taking cyclosporine did not have a higher incidence of increased serum creatinine compared with patients who did not receive cyclosporine.…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…1,4,5,27 In this report, the increases in serum creatinine were all below 2 times ULN. Patients taking cyclosporine did not have a higher incidence of increased serum creatinine compared with patients who did not receive cyclosporine.…”
mentioning
confidence: 74%
“…1-6, [26][27][28][29][30] Two studies in patients with thalassemia (one conducted in children) reported no significant difference in post-treatment serum ferritin levels following deferasirox versus phlebotomy.…”
Section: Adverse Event N (%) All Severementioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study of 76 nonthalassemic patients, the authors reported a deferasirox-induced negative iron balance in 84% of patients after initiating it at a median of 168 days after HSCT. The drug-related adverse events were increased blood creatinine (26%), nausea (9%), and abdominal discomfort (8%) [71]. …”
Section: Management Of Iron Overloadmentioning
confidence: 99%